2008
DOI: 10.1016/j.pbiomolbio.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Late sodium current in failing heart: Friend or foe?

Abstract: Most cardiac Na + channels open transiently upon membrane depolarization and then are quickly inactivated. However, some channels remain active, carrying the so-called persistent or late Na + current (I NaL ) throughout the action potential (AP) plateau. Experimental data and the results of numerical modeling accumulated over the past decade show the emerging importance of this late current component for the function of both normal and failing myocardium. I NaL is produced by special gating modes of the cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 130 publications
1
91
0
Order By: Relevance
“…Increased expression of Na v 1.5 is expected to lead to an increase in I Na density, as is the increased expression of Na v β1 (Na v β1 increases I Na density when expressed with Na v 1.5; Nerbonne & Kass, 2005). An increase in I Na density could help explain the increase in APD with age, because the late Na + current (I Na,L ) can affect APD (Maltsev & Undrovinas, 2008). However, in canine right atrium, I Na density does not change with age (Baba et al 2006), and the AP upstroke velocity is reported to decrease with age in rat right atrium (Cavoto et al 1974).…”
Section: Age-dependent Increase In Apdmentioning
confidence: 99%
“…Increased expression of Na v 1.5 is expected to lead to an increase in I Na density, as is the increased expression of Na v β1 (Na v β1 increases I Na density when expressed with Na v 1.5; Nerbonne & Kass, 2005). An increase in I Na density could help explain the increase in APD with age, because the late Na + current (I Na,L ) can affect APD (Maltsev & Undrovinas, 2008). However, in canine right atrium, I Na density does not change with age (Baba et al 2006), and the AP upstroke velocity is reported to decrease with age in rat right atrium (Cavoto et al 1974).…”
Section: Age-dependent Increase In Apdmentioning
confidence: 99%
“…A recent study has shown that SCN1B gene silencing caused increased I NaP as a result of increased expression of SCN5A in the SCN1B-null mice (14) . The biophysical properties of I NaP recorded in the SCB1-null mice, however, have not been fully examined, which makes it difficult to compare them with well-known properties of the slowly inactivating I NaL reported in a variety of species including humans, dogs, guinea pig, rabbit, and rat (26). To explain the augmented I NaP in SCN1B-null mice, Lopez-Santiago et al (14) suggest a transcriptional regulation mechanism.…”
Section: Molecular Mechanisms Of I Nal Modulation By Na V ␤ 1 and Na mentioning
confidence: 99%
“…5 and 6), 2) decrease beat-to-beat APD variability, and 3) improvement of Ca 2ϩ handling and contractility (22,25,41,42,44). Accordingly, I NaL has emerged as a novel target for cardioprotection to treat the failing heart (24,26,34). The fact that I NaT is decreased but I NaL is increased in HF (21,23,25,42,45,48) suggests that not all NaCh must be equally targeted.…”
Section: Physiological Significancementioning
confidence: 99%
“…The reduced repolarization reserve of old cardiomyocytes may have enhanced the function of the late Na ϩ current (I NaL ), which is operative in the plateau and repolarization phases of the AP. The prolonged repolarization may have sustained Na ϩ influx via I NaL , a factor that may contribute to the slower electrical recovery in old cells, with important implication on intracellular ionic homeostasis (3,22,54,55).…”
Section: Physiological Aging Alters Ventricular Performancementioning
confidence: 99%
“…The prolongation of the AP has important implications in the excitation contraction-coupling of old cardiomyocytes. (8,13,22,31,38,(41)(42)(43)(44)48).…”
Section: Physiological Aging Alters Ventricular Performancementioning
confidence: 99%